History of domestic violence and health service use among mid‐aged Australian women - Deborah Loxton; Margot Schofield; Rafat Hussain (Elsevier, 2004)
Abstract Objectives:To examine associations between history of domestic violence and health service use among mid‐aged Australian women, adjusting for physical and psychological health status and demographic factors. Methods:Population‐based cross‐sectional postal survey (1996) of the Australian Longitudinal Study on Women's Health. Of 28,000 women randomly selected, 14,100 (53.5%) aged 45-50 years participated. Logistic regressions were used to assess associations between domestic violence and health service use. Results:After adjusting for demographic variables, multivariate analysis revealed associations between ever having experienced domestic violence and three or more consultations in the previous 12 months with a family doctor (OR 2.07, 95% CI 1.68-2.55), hospital doctor (OR 1.77, 95% CI 1.44-2.17), or specialist doctor (OR 1.54, 95% CI 1.35-1.75), or being hospitalised (OR 1.36, 95% CI 1.20-1.54). After adjusting for demographic variables and physical and psychological health status, these associations were attenuated: three or more consultations with family doctor (OR 1.36, 95% CI 1.09-1.70), hospital doctor (OR 1.16, 95% CI 0.92-1.45), or specialist doctor (OR 1.14, 95% CI 0.98-1.32), and being hospitalised (OR 1.10, 95% CI 0.96-1.26). Conclusions:Physical and psychological status accounted for the associations between domestic violence and higher health service use, with the exception of GP consultations, which remained associated with domestic violence. Implications:Physical health status only partially explains the increased health service use associated with domestic violence, while both physical and psychological health status explained higher usage of specialist and hospital services. It seems likely that women who have experienced domestic violence may be seeking consultations from GPs for reasons additional to health status.